Effect of NaCl salinity on growth and pigment system of Fagopyrum esculentum Moench. and Vicia faba L. - Деркач, І. В.; Романюк, Н. Д. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Growth dynamics, chlorophylls and pheophytins level in broad beans and buckwheat plants under the NaCl impact for 7–14 days in sand culture have been studied. Increasing the salt concentration in the substrate caused growth inhibition, decrease of the plant leaf area, fresh and dry mass. For almost all variants there was observed negative correlation between increasing salt concentration and pigments content. The differences in reactions of plants pigment system under toxicant impact were revealed. In the buckwheat leaves after 7 days of exposure to 100 mM NaCl and after 10 days of 120 mM NaCl treatment chlorophylls and pheophytins content sharply increased. After 10 and 14 days of NaCl exposure there was observed decrease in the total sum of chlorophyll and pheophytins and decrease of the chlorophyll a/b ratio. In bean leaves total chlorophyll decreased just by 19–32 % at 300 mM NaCl, whereas 250 mM NaCl for 10 and 14 days did not significantly affect this value. Pheophytins level in bean leaves decreased by 7 and 10 days of exposure to the salt and increased for 18–27 % at 14 day of experiment. Chlorophyll a/b ratio in beans, unlike buckwheat, at all time points was higher than in the control. Revealed changes in the pigments levels in buckwheat and beans plants, probably, caused by species differences in the ways of accumulation and transporting toxic ions and the mechanisms of adaptation to their action.